The role of tourism growth in generating additional energy consumption: empirical evidence from major tourist destinations - Katircioglu, Salih; Gokmenoglu, Korhan K.; Eren, Baris Memduh (Springer, 2019)
This study investigates the role of tourism growth in generating additional energy consumption in the case of major tourist countries. Panel data that range from 1995 to 2014 have thus been constructed. Significant results of this study confirm long term economic effects of tourism growth in energy usage in tourist destinations; tourism exerts positively significant but inelastic effects on the overall energy consumption. Finally, this study finds that changes in exchange rates cause changes in tourism and changes in tourism cause significant changes in energy consumption in the same direction; therefore, it is proposed that tourism sector acts as a successful mediator between exchange rate changes and energy consumption which is an essential policy concern for countries heavily depending on foreign energy imports.
Keywords: Energy consumption; Exchange rates; Tourism; Urbanization